A comparative life-cycle assessment of hydro-, nuclear and wind power: A China study. (1st September 2019) - Wang, Like; Wang, Yuan; Du, Huibin; Zuo, Jian; Yi Man Li, Rita; Zhou, Zhihua; Bi, Fenfen; Garvlehn, McSimon P.
Highlights: A life-cycle comparison of three clean energy technologies is conducted. The evaluation covers not only the GHG emissions but also other impact categories. An example is provided to showcase the proposed evaluation method. Abstract: Energy sector is one of biggest contributors to the Greenhouse Gas (GHG) emissions. As a result, it has attracted considerable attention to reduce the GHG emissions of electricity production. Hydro-electric, nuclear and wind power are the top three clean energy in China. In this study, the environmental impacts of these three technologies are analyzed, assessed and compared via a life-cycle assessment approach. The entire life cycle, including the manufacturing, construction, operation and decommissioning stages is examined. Apart from global warming potential (GWP100) caused by GHG emissions, the environmental impacts assessed in this study also included acidification potential (AP), eutrophication potential (EP), photochemical ozone creation potential (POCP) and human toxicity potential (HTP). The results show that wind power technology has the most significant environmental impacts amongst these three clean energies, followed by nuclear power and hydropower. For example, in terms of global warming potential, wind power produces 28.6 ± 3.2 g CO2 -eq/kWh of GWP100 throughout its life cycle, which is higher than that of nuclear power (12.4 ± 1.5 g CO2 -eq/kWh) and hydropower (3.5 ± 0.4 g CO2 -eq/kWh). In addition, this study revealed that the the manufacturing stage is the largest contributor of environmental impacts for wind and hydropower. By contrast, the decommissioning stage is most significant for nuclear power in terms of environmental impacts. The comparative life cycle assessment method proposed in this study provides useful tool for the future environmental assessment of electricity production technologies. Findings of this study provide useful inputs for the sustainable transformation of the energy sector.